Business Managements of the Production and Rice Processing Certified the Good Agricultural Practice: A Case study of Large – Scale Paddy Field of Farmers Group, Ban Talunglek, Tambon Mainapeang, Wangyai District, Khon Kaen Province - Doneicha, Wilawan; Poungchompu, Supaporn (WMS Journal of Management, 2020)
The objective of this research was to investigate 1) the group management characteristics of the production and rice processing, 2) the satisfaction of farmers participation as members of large - scale paddy field, Ban Talunglek, Tambon Mainapeang, Wangyai District, Khon Kaen Province. The research studied from 2 sample groups (6 representatives of the board with Purposive sampling method and Depth Interview method, 40 farmer member group representatives by using a questionnaire). The result showed that the type of management has separated operations into 4 parts as follows: Production Input Management, Production and Quality Control of rice production and rice processing, Marketing and price determination, Financial Management. However, the operation also encountered cost problems because of non-recording and the memorandum of understanding (MOU) with the rice mill. In terms of the products processed from rice faced production problems and the shortage of production inputs. As for satisfaction, it was found that farmers were satisfied at a high 5 levels of section, consisting of 1) participation in membership and ease of operation 2) supporting inputs of production 3) knowledge transfer 4) marketing and price of rice 5) agricultural machinery services. Suggestions for group operations: 1) it should have a work record especially in finance. 2) the processing should have a systematic production plan. 3) Financial details should be clarified. For government 1) there should be an officer to teach accounting to the board. 2) For Memorandum of Understanding (MOU), it should consider rice mills nearby in the area.